Patients' views on a proposed oral cancer screening technology. Issue 3 (April 2022) - Orchard, A.; Sunny, S.P.; Suresh, A.; Birur, P.; Kuriakose, M.; Prabhu, S.
Abstract: Brush cytology and telemedicine platforms are used with proven benefits in remote diagnosis of malignancies like cervical cancer. In low-resource settings access to the current standard of care, biopsy and histopathology grading of oral lesions, can be unfeasible. Risk-stratifying early malignant and oral potentially-malignant lesions can help instigate therapeutic treatment and improve prognosis. Therefore, a telecytology platform enabling remote connectivity to specialist centres may aid early detection of oral cancer. We outline head and neck (H&N) cancer patients' views on an oral brush cytology investigation.